Red Clays And Red Soils Of Hungary - Fekete, József (JOURNAL OF LANDSCAPE ECOLOGY, 2010)
Hungarian red clays are the result of soil formation from previous geologic periods. They were spread over areas which were dry during the Tertiary Period and were not covered by sediments. The climate of the Quaternary Period eroded them, so that today they can only be found in areas where they were protected against degradation or where their thickness and resilience could withstand the forces of erosion. Thus, red clays are fossil or relic products of soil formation. Since both their water regime and nutrient supply differ from soil in the Holocene, their economic importance is far from negligible, vineyards, forests and arable cultivation can by found on these areas. Their influence may by seen in more extensive territories where they were washed away, settled and became mixed with other soils.